Phlebotomy : worktext and procedures manual - Warekois, Robin S.; Robinson, Richard (St. Louis, Missouri : Elsevier Science, 2016)
With an illustrated, storyboard format for procedures, Phlebotomy: Worktext and Procedures Manual, 4th Edition describes all aspects of phlebotomy, with current coverage of equipment, safety procedures, arterial blood gases, point-of-care testing, and practical phlebotomy skills. Procedures cover core functions and are outlined with step-by-step instructions and new full-color photos. Clinical scenarios, practice tips, and new Avoid That Error features keep the focus on application and practice. Written by phlebotomy expert Robin Warekois, this practical worktext also includes competency checklists, a mock certification exam, a detachable bookmark that can serve as a tube guide, and a new video collection on the Evolve companion website.
Introduction to phlebotomy -- Phlebotomy basics -- Specimen collection -- Specimen handling -- Professional issues.
Includes bibliographical references and index.
Keywords: PHLEBOTOMY